Marsdenia tenacissima extract alters crucial metabolites in cancer, determined by 1H NMR based metabolomics approach (Brazilian Journal of Pharmaceutical Sciences, 2018)
Altered metabolites level in the biosystems, is the potential cause of cancer, the primary reason of alteration of metabolism is change in nutrient consumption and waste excretion, as a result genetic mutation leads to cancer initiation and progression. Aberration of specific metabolites such as fumarate, succinate, 2-hydroxyglutarate may alter cell signaling. We collected liver and kidney samples and prepared for 1 H NMR analysis, then executed NMR spectroscopy. We used a set of domestic R scripts to perform an unsupervised principal component analysis (PCA) and a supervised orthogonal signal correction partial least-squares discriminant analysis (OSC-PLS-DA). It signifies class discrimination for getting a clear separation, whereas PCA scores plot signifies the model group kept further away from the control group than drug group on the horizontal axis. In another PCA scores plots, most parts of the control group was overlapping with the drug group but was distant from the model group. Marsdenia tenacissima extract (MTE) (Chines name: Xiao-Ai-Ping, XAP) modulates level of crucial metabolites such as fumarate, lactate, succinate, determined by 1 H NMR spectroscopy and their altered level contributes major role in cancer.